2001
DOI: 10.1116/1.1392397
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and etching properties of dual ion beam deposited hydrogen-free silicon nitride films

Abstract: Articles you may be interested inEffects of increasing nitrogen concentration on the structure of carbon nitride films deposited by ion beam assisted deposition Mechanical properties and residual stress in AlN/Al mixed films prepared by ion-beam-assisted depositionThe synthesis, characterization, and mechanical properties of thick, ultrahard cubic boron nitride films deposited by ion-assisted sputtering Hydrogen-free silicon nitride (SiN x ) with x varying from 0 to 1.3 were prepared by sputtering a Si target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The nanoindentation was used for measurement of the properties of SiLK [19]. In case of the properties of tantalum and silicon nitride thin films, a large scatter was observed according to processing conditions such as thickness [21], temperature [22], and contents of nitrogen [21,23], etc. Therefore the well-known bulk properties of tantalum [24] and silicon nitride [25] which are in the range of reported thin film properties of them were adopted in FEA.…”
Section: Model Descriptionmentioning
confidence: 99%
“…The nanoindentation was used for measurement of the properties of SiLK [19]. In case of the properties of tantalum and silicon nitride thin films, a large scatter was observed according to processing conditions such as thickness [21], temperature [22], and contents of nitrogen [21,23], etc. Therefore the well-known bulk properties of tantalum [24] and silicon nitride [25] which are in the range of reported thin film properties of them were adopted in FEA.…”
Section: Model Descriptionmentioning
confidence: 99%
“…5. 13 For silicon nitride films prepared by LPCVD process involving species with thermal energies as low as ≈0.1 eV, the internal stress is tensile and falls in the range of 0.29 to 1 GPa. This result is rather close to 〈E SiN *〉, further supporting the validity of the microbridge method.…”
Section: A Single-layered Silicon Nitride Microbridgesmentioning
confidence: 99%
“…The structure of plasma deposited silicon nitride films has been studied by Knolle and Osenbach [12], they used the random binding model to calculate electronegativities for the aSiN:H films. The various properties of Si 3 N 4 deposited films by using PECVD system; electron cyclotron resonance PECVD, helical resonator plasma reactor and dual frequency rf source have been reported by many researchers [3,[13][14][15][16][17][18][19]. Hsieh et al [20] have reported the influence of various kinds of gases along with their flow ratios on the a-SiN x :H films.…”
Section: Introductionmentioning
confidence: 96%